Stokes-parameter analysis of the polarization of light transmitted through a chiral nematic liquid-crystal cell - Woon, K.L.; O'Neill, M.; Richards, G.J.; Aldred, M.P.; Kelly, S.M. (Optical Society of America, 2005)
A spectroscopic Stokes polarimeter is used to directly measure the linearly, circularly, and randomly polarized components of light obtained on transmission of unpolarized light through thick chiral nematic liquid-crystal cells in the stop band. The Stokes parameters are simulated to fit the experimental data by use of the Berreman 4 × 4 transfer matrix by means of the Jones and Stokes vectors and taking into account multiple reflections at the interfaces of the cell. Excellent agreement is obtained. The transmitted light through a commercial cell is mainly circularly polarized at normal incidence, but a significant linearly polarized component is also observed. The model shows that this results from refractive-index mismatching at the liquid-crystal–alignment-layer interface, but a small linearly polarized component remains even with optimized index matching. An improved device configuration incorporating random defects at the exit boundary of the liquid crystal gives a highly circularly polarized output with virtually no linear or unpolarized components.